2019
DOI: 10.1177/1120700019841579
|View full text |Cite
|
Sign up to set email alerts
|

Traction force for peroperative hip dislocation in hip arthroscopy

Abstract: Objectives: Traction force widens the joint space during hip arthroscopy. It is unclear how much the traction force varies and if it is related to the joint space widening. Main goal of our study was to measure the amount of force needed to widen the hip joint. Second goal was to study the relation between this force and the amount of joint space widening. Methods: Traction force was measured in 27 patients (of whom 24 female, mean age 41) during arthroscopy. Measurements were performed before the procedure, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
(25 reference statements)
0
16
2
Order By: Relevance
“…Roling et al . [ 14 ] measured the effects of both venting and capsulotomy on traction force with a desired initial distraction distance of 10 mm. The authors found a 16% reduction in traction force after venting and a 9% reduction in traction force following capsulotomy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Roling et al . [ 14 ] measured the effects of both venting and capsulotomy on traction force with a desired initial distraction distance of 10 mm. The authors found a 16% reduction in traction force after venting and a 9% reduction in traction force following capsulotomy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] and Roling et al . [ 14 ] documented the change in traction force after each intervention but did not report corresponding changes in distraction distance which presumably occurred, as neither study specifically fixed the distraction distance. The current data suggest that distraction distance increases over the course of venting and capsulotomy by ∼1.50–2.25 mm on average, depending on the size of the femoral head.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We read with great interest and appreciation the article titled “Traction force for peroperative hip dislocation in hip arthroscopy” by Röling et al 1 that appeared in Hip International in April 2019.…”
mentioning
confidence: 99%